PENGARUH METODEL ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA DI SDN 33 PONTIANAK UTARA - Siregar, Ernawati; Marzuki, Marzuki; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract.From the results of interviews at North Pontianak Public Elementary School 33, it is known that speaking skills of VA class students are still below the completeness standard, that is there are 17 students from 28 students who have not yet completed the aspect of speaking. Inner problem this research is "Is there any influence of the Role Playing method on speaking skills in North Pontianak 33 public schools? ". Research method used is an experimental method, while the research form used is one group pre-test and post-test. The population in this study was all class V students of North Jakarta 33 public elementary schools. In this research the sample is 28 VA students. Technique Data collectors used in this study are measurement techniques with score on students' speaking skills. Based on the results of data analysis from the mean value of the pre-test 67.14 and the average post-test 75.72. The results of the t test obtained by t table at a significant level (Î±) = 0.05% is 1.703. Because of thitung (7.94) ttable (1.703) then the post-test data is received. So that there is the effect of applying the Role Playing method to the speaking skills of participants educated in class V North Pontianak 33 State Elementary School. From the calculation of the effect size (ES), obtained at 0.1154 (low category).Â Keywords: Method of Role Playing, Speaking Skills, Indonesian LanguageÂ